Patterned Fabric Image Retrieval Using Color and Space Features (Journal of Fiber Bioengineering and Informatics, 2015)
Image retrieval has been an active research topic in the last decade. As one of the promising approaches,color histogram based image retrieval has been attracted by many researchers. However, it is sensitiveto noisy interference and lost any spatial information. To overcome drawbacks, the algorithm combinedweighted color histogram with image segmentation is proposed for patterned fabric images in thispaper. Firstly, the patterned fabric images are preprocessed using image enhancement. Secondly,color and spatial information features are respectively extracted by weighted color histogram and imagesegmentation method, which are transformed into feature vectors. Finally, the similarity betweenobjective image and image database is calculated with Euclidean distance. The retrieval results aredisplayed in decreasing order of similarity. Experimental results, including comparisons with colorhistogram algorithm and weighted color histogram algorithm, demonstrate the effectiveness of proposalfor patterned fabric images.
Keywords: Image Retrieval; Image Enhancement; Weighted Color Histogram; Image Segmentation; Similarity